Development of Pistachio Plantations in the Southern Regions of the Republic (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
At present, various types of pistachio tree seedlings in the state forestry and farms of the country are grown. The family of pistachio trees includes tropical and subtropical shrubs and trees, with some species spread in temperate areas. In general, it is advisable to establish pistachio plantations in Uzbekistan in regions with not less than 300 mm of annual rainfall. Such areas include mountain regions like Boboq and Samarkand. To achieve higher pistachio yields, selecting promising varieties based on evaluation is essential.